Effect of Natural Growth Regulators on the Growth of Coffee Seedlings in the Cotyledon Phase - Mismawarni Srima Ningsih; Syafrison; Fardedi; Giska Oktabriana; Mela Rahmah; Hary Yanto Jailani; Bungaini; Nurpiati; Rahmat Kurniawan (Jurnal Riset Perkebunan, 2024)
Coffee is an important agricultural commodity with increasing global demand, so optimizing the growth of coffee seedlings, especially during the seedling phase, is crucial to increase productivity. The use of natural plant growth regulators offers an environmentally friendly and economical solution. This study aims to evaluate the effect of natural plant growth regulators from onion extract and bean sprout extract on the growth of robusta coffee seedlings (Coffea canephora L.) during the seedling phase. The study was conducted using a Randomized Block Design (RBD) with three treatments, namely control, onion extract, and bean sprout extract. The parameters measured included plant height, stem diameter, and number of leaves for six weeks. Data were analyzed using ANOVA and BNT test at the 5% level. The results showed that both natural plant growth regulators significantly increased the growth of coffee seedlings compared to the control. Bean sprout extract gave the best results for plant height (16.75 cm), while onion extract was superior in increasing stem diameter (4.65 mm) and number of leaves (12.20). Statistical analysis confirmed significant differences between treatments and controls for all parameters. Thus, the use of onion and bean sprout extracts as natural growth regulators has proven effective in increasing the growth of coffee seedlings in the seedling phase, offering an environmentally friendly and economical alternative for optimizing the growth of coffee seedlings.